Survival and Effect of Exopolysaccharide-Producing Lactobacillus plantarum YW11 on the Physicochemical Properties of Ice Cream - Zhang Jian; Zhao Wen; Guo Xialei; Guo Ting; Zheng Yi; Wang Yuetong; Hao Yijiang; Yang Zhennai (Polish Journal of Food and Nutrition Sciences)
Ice cream was prepared with exopolysaccharide (EPS)-producing Lactobacillus plantarum YW11 by direct inoculation (DI), addition of pre-fermented skim milk (FSM), or addition of the lyophilized powder of the YW11 strain (LP) into the ice cream mix. After 4 weeks of storage, viable counts of the YW11 strain decreased in all groups by 0.8–1.61 log cfu/g. Furthermore, ice cream made using the LP method showed the highest survival rate. The ice cream processing and storage conditions also affected the YW11 strain’s tolerance to acid and bile, with a decrease in survival rate of 38.8–63.2% and 10.8–51.8%, respectively. The degree of impact on the viability of strain YW11 was hardening>aging>freezing>storage (p<0.05). The YW11 strain produced a ropy EPS (up to 4.84 mg/g) in the ice cream mix made using the DI and FSM methods; it was present as a fine porous matrix as observed by Cryo-SEM. Formation of the EPS together with changes in the pH of the ice cream mix caused increased viscosity (up to 131.0 mPa·s), overrun and meltdown, decreased destabilization of fat, and firmness of ice cream. Hydrocarbons, ketones, and benzenes were found to be the major volatiles in the fermented ice cream samples, which also had decreased levels of dodecane, characterized by the smell of dirt.